Root Morphological Traits of Seedlings Are Predictors of Seed Yield and Quality in Winter Oilseed Rape Hybrid Cultivars - Louvieaux, Julien; Spanoghe, Martin; Hermans, Christian (Frontiers in Plant Science, 2020)
The root system is responsible for soil resources acquisition and hence, optimizing crop root characteristics is of considerable significance for agricultural production. This study evaluated a panel of twenty-eight European modern cultivars of oilseed rape (Brassica napus L.) cultivated in laboratory and field environments. Root morphology was screened using a high-throughput hydroponic growth system with two divergent nitrogen supplies. The panel showed an important diversity for biomass production and root morphological traits. Differences in root and shoot dry biomasses and lateral root length were mainly explained by the genotype, while differences in primary root length by the nutrition. The cultivars were tested in a pluriannual field trial. The observed variation for yield and seed quality traits attributed to the genotype was more important than the year or the genotype x year interaction effects. The total root length measured in laboratory culture could predict the proportion of nitrogen taken up from the field and reallocated to seed organs, a component of the nitrogen use efficiency. The genetic interrelationship between cultivars, established with simple sequence repeat markers, indicated a very narrow genetic base. Positive correlations were found between the genetic distance measures, root morphological trait during nitrogen depletion and yield components. This study illustrates a root phenotyping screen in the laboratory with a proof of concept evaluation in the field. The results could assist future genetic improvements in oilseed rape for desirable root characteristics to reduce nutrient losses in the environment.